Reforma al art. 77 de la ley de hidrocarburos para regular apropiadamente las sanciones pecuniarias, evitando el exceso de discrecionalidad para multar de la agencia de regulación y control hidrocarburífero - Suarez Vásquez, Hever Daniel (2016)
The legal issues concerning this investigation is aimed at legal analysis of the punitive administrative proceeding regime for violations of the Hydrocarbons Law and its implementing regulations, constituting an important place within the scope of public law which is directly related to natural resources nonrenewable and the control and regulation of the same is done by the competent authorities. The theme is part of Administrative Law, as will investigate legal phenomena from the complex relationships that operate between the Administration and the Administered, which aims on the one hand impose administrative will framed in legal norms and principles, and on the other, claim for the damages to individual rights that may occur as a result of an illegal or inaccurate action by the Administration. The legal problem is what to try and meet focuses on legal connotations surrounding the administrative procedure involved punishment for violation of the Hydrocarbons Law and its implementing regulations; the same that is initiated by the highest authority on hydrocarbons to impose administrative sanction for acts or omissions subject to control hydrocarbon legislation, I mean the marketer and distributor of liquid hydrocarbon fuels (gasoline, diesel ), liquefied petroleum gas for domestic or industrial use; Dl art. 78 cited below, we see that so that the hydrocarbons law sets penalties for violators of the regulations in this area: "Art. 77. Failure of the contracts signed by the Ecuadorian government for exploration and / or exploitation of hydrocarbons, and / or infringement of the law and / or regulations, which do not produce effects of expiration will be sanctioned in the first occasion with a fine up to five hundred basic unified salaries for workers in general; the second time with a fine of five hundred to one thousand unified basic remunerations for workers in general; and the third time with a fine of 1000-2000 unified basic remunerations for workers in general, the same that will be imposed by the Director of the Agency for Regulation and Hydrocarbon Control giving reasons, using objective criteria of assessment, such as: seriousness of the breach, negligence, damage occurred, scope of remediation, turnover, damage to the state and consumers and others deemed relevant infringement keeping proportionality in accordance with what is established in the Regulations." From the foregoing it follows standard first that there is an excessive regulation of sanctions that exceeds in most cases the actual economic capacity of the control subjects of this law according to their income; secondly these endpoints the Director of the Agency for Regulation and Control Hydrocarbon to sanction becomes unenforceable, these parameters too subjective to have led to abuses and excesses of the power of discretion of public authorities, which have affected rights marketers and distributors of liquid hydrocarbon fuels (gasoline, diesel) and liquefied petroleum gas for domestic or industrial use, thus violating the principle of proportionality rule indicates that it should be noted, because in practice it is undeniable that fines do not keep a real balance to the damage produced, and is also disproportionate to turnover. Against this background, it is necessary and imperative to raise a necessary reform to art. 77 of the Act in question to ensure the effective protection of the rights of control subjects of this law, access to justice in an effective and transparent manner, even adding the feasibility challenge in administrative or contentious administrative sanctions by the Agency for Regulation and Control Hydrocarbon (ARCH) without the need to present as a requirement for the appeal, proof of payment of the fine.